Relationship of Resilience Factors With Biopsychosocial Markers Using a Comprehensive Home Evaluation Kit for Depression and Suicide Risk: A Real-World Data Analysis - Jang, Sooah; Choi, Sun-Woo; Ahn, Ryunsup; Lee, Ju-Yeal; Kim, Joohan; Seok, Jeong-Ho (Frontiers in Psychiatry, 2022)
Objectives: Adverse childhood experiences (ACEs) are fundamental factors of developing depression with increased suicide risk. Resilience is considered an important protective factor that can prevent trauma survivors from developing depression. We developed a home evaluation kit for comprehensive assessment of bio-psycho-social factors related to depression and suicide. This kit contained a psycho-social evaluation battery, named the Protective and Vulnerable factors battery questionnaire (PROVE) comprising of depressive symptoms and suicide risk, as well as various depression-related psychosocial factors such as ACE, resilience, mentalization capacity, and attachment via online survey tools. Furthermore, salivary cortisol levels were used as biological indicators to assess the hypothalamus-pituitary-adrenal axis function. Methods: Real-world data analysis was made out of data collected from participants who visited CHEEU Counseling center or Gangnam Severance hospital for mental health check-up. The participants were put into three mental state groups (green-normal, yellow-borderline, and red-risk) depending on the result of PROVE battery. The difference between psycho-social factors and salivary cortisol indicators by group was identified by analysis of covariance with sex and age as covariates. Linear regression analysis was conducted to find significant association of resilience score with other bio-psycho-social variables such as ACE, attachment, mentalization or post-awakening cortisol concentrations (area under the curve respect to ground, AUCg). Partial correlation analysis was performed to evaluate the relationship of AUCg with psychosocial factors. Results: Depression-related psycho-social indicators were significantly different among groups. Insecure attachment and the mentalization problem are negatively influencing factors to resilience. Furthermore, the severity of depression in participants with ACE was also influenced by mentalization problem. AUCg was different according to the PROVE group, presence of ACE or resilience level. In addition, AUCg showed a positive correlation with resilience score but negative correlations with depressive symptom, ACE, mentalization problem, and anxiety or avoidance attachment. Conclusion: This study suggests that there are some key factors negatively affecting resilience: insecure attachment and mentalization problem. In groups with ACE, a mentalization problem was suggested as a factor that can increase depressive symptoms. AUCg was associated with resilience as well as several other vulnerable factors of depression, showing its potential as a promising biomarker.